2012
DOI: 10.1590/s0004-27302012000700003
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency among newly diagnosed youth-onset diabetes mellitus in north India

Abstract: OBJECTIVES: Vitamin D deficiency is common at all ages, and low levels of vitamin D have been associated with high incidence of type 1 diabetes. Similar results are not consistent for type 2 diabetes. The aim of the present study was to estimate vitamin D status in newly detected youth-onset diabetes in north India. SUBJECTS AND METHODS: This was a prospective case control study at a tertiary care hospital in north India. Seventy two newly detected youth-onset diabetes subjects (age < 25 years), and 41 age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 39 publications
5
43
2
2
Order By: Relevance
“…Moreover, in an experimental animal model of T2D (obese Wistar rats) without Vit D deficiency, Vit D was found to decrease plasma glucose concentrations by as much as 40% (de Souza Santos & Vianna, 2005). The maternal serum 25-hydroxy Vit D 3 concentrations in both the GDM and IGT groups at 24-28 weeks of gestation were significantly lower than that of the non-GDM controls and inversely related to the fasting glucose and insulin concentrations (Daga et al, 2012;Nikooyeh et al, 2011). Palomer et al (2008) found that Vit D replenishment improves glycemia and insulin secretion in patients with T2D and established hypovitaminosis D. Boucher (2011) reported that the mechanism of action of Vit D in T2D is thought to be mediated not only through the regulation of calcium trafficking in b-islet cells -which regulate insulin synthesis, secretion, sensitivity, and high calcium intake and that have been found to be inversely associated with body weight and fatness -but also through direct action on pancreatic b In peripheral insulin-target cells, active Vit D metabolites may enhance insulin sensitivity in several ways, including through an increase in the expression of insulin receptors (Maestro et al, 2002), the activation of transcription factors important in glucose homeostasis (Dunlop et al, 2005), or indirectly via the regulation of calcium, which is essential for insulin-mediated intracellular processes.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in an experimental animal model of T2D (obese Wistar rats) without Vit D deficiency, Vit D was found to decrease plasma glucose concentrations by as much as 40% (de Souza Santos & Vianna, 2005). The maternal serum 25-hydroxy Vit D 3 concentrations in both the GDM and IGT groups at 24-28 weeks of gestation were significantly lower than that of the non-GDM controls and inversely related to the fasting glucose and insulin concentrations (Daga et al, 2012;Nikooyeh et al, 2011). Palomer et al (2008) found that Vit D replenishment improves glycemia and insulin secretion in patients with T2D and established hypovitaminosis D. Boucher (2011) reported that the mechanism of action of Vit D in T2D is thought to be mediated not only through the regulation of calcium trafficking in b-islet cells -which regulate insulin synthesis, secretion, sensitivity, and high calcium intake and that have been found to be inversely associated with body weight and fatness -but also through direct action on pancreatic b In peripheral insulin-target cells, active Vit D metabolites may enhance insulin sensitivity in several ways, including through an increase in the expression of insulin receptors (Maestro et al, 2002), the activation of transcription factors important in glucose homeostasis (Dunlop et al, 2005), or indirectly via the regulation of calcium, which is essential for insulin-mediated intracellular processes.…”
Section: Discussionmentioning
confidence: 94%
“…Studies from India have also reported hypovitaminosis D in a significant number of people with T1D and in youth onset both in T1D and T2D. [78] In view of scarce data on vitamin D status in T2D patients from India, the present study was undertaken to assess the vitamin D status in newly detected T2D patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the months with the most frequent diagnosis of T1DM were January and February (and the ones with least diagnoses were May, June, and July), which could be closely connected to the fact that respiratory infections are common during these months and that there is a lack of exposure to sunlight which -a lower D vitamin intake -could further contribute to the incidence of T1DM. (15) …”
Section: Discussionmentioning
confidence: 99%